High Prf Metal Vapor Laser Active Media For Visual And Optical Monitoring; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Torgaev S. N. Stanislav Nikolaevich; Trigub M. V. Maksim Viktorovich; Evtushenko G. S. Gennady Sergeevich; Evtushenko T. G. (2016, 2016)
Title screen